Pengaruh Penerapan ISO 9001:2008 Terhadap Kepuasan Pelanggan (Pasien) Pada Balai Pengobatan PT. Kertas Leces (Persero) di Probolinggo - Hermanto Hermanto (Ecobuss, 2016)
Global challenges can not be avoided either from government or private sector, like it or not all parties are required to prepare themselves to be able to survive the standardization of management has become a major issue, more specifically the standardization of quality management systems (ISO 9001:2008). To that end, the government and private agencies need to set up the framework of the system towards a desired quality of the institution in accordance with the goals and objectives. Through human resources, infrastructure and working environment of the application of ISO 9001:2008 in the sense that the goal or objective quality of an institution capable of achieving conformity with the wishes of the expected (customer satisfaction) or a partner institution. Analyizing the effect of the Implementation of ISO 9001:2008 (human resources, infrastructure and work environment) to customer/patient satisfaction simultaneously or partially at the Medical Center PT. Kertas Leces (Persero). Descriptive and inferential analytic study with purposive sampling 50 respondents questionnaire instrument, Likert scale and multyple regression analysis techniques with a (0.05). Implementation of ISO 9001:2008 (human resources, infrastructure and work environment) with the F test, sig (0.000) < a (0.05), and Fcount (92.530) > Ftable (2.8068) simultaneously is very significant effect to Customer satisfaction with simultaneously determination contribution (85,8%). Variables: Human resources sig (0.000) < a (0.05) and tcount (5.728) > ttable (1.679) partially was very significant with (0.719) partially effect to customer satisfaction, Infrastructure with sig (0.128) > a (0.05) and tcount (1.549) < ttable (1.679) partially was not significant, and the working environments with sig (0.03) < a (0.05) and tcount (3.082) > ttable (1.679) partially was significantly affected by the partial contribution (0.494) to customer satisfaction. Thus showing the good human resources, infrastructure and work environment, the higher level of customer satisfaction. Keywords: Implementation ISO 9001:2008, Human Resources, Infrastructure, Work Environment, and Customer/patient Satisfaction.